2008
DOI: 10.1111/j.0908-8857.2008.04109.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and developmental effects, and morphological influences on the acoustic structure of individual distance calls in female Bengalese finchesLonchura striatavar.domestica

Abstract: Recent studies of the vocal mechanisms of songbirds have shown that there are physical effects on sound production. Interspecific and phylogenetic comparisons have shown that body mass and bill morphology are two major factors affecting vocalizations such as songs. We analyzed the distance calls of female Bengalese finches Lonchura striata var. domestica, the non-vocal learning sex, to assess the potential physical effects on the acoustic structure of vocalizations. By experimentally controlling rearing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(78 reference statements)
2
1
0
Order By: Relevance
“…Our estimates of phylogenetic inertia provide further evidence that power distribution and spectrotemporal features are minimally constrained in their evolution (i.e., low phylogenetic inertia), suggesting that these features may reflect the plasticity needed to alter song features for inter- and intra-specific competition. Analyses using ppMantel tests showed that body size is correlated with frequency features in our species, a common finding in animals including birds 53 , 84 , 85 . Previous studies suggest that changes in frequency features may be constrained to changes in morphological features associated with body size such as size of the organs that produce (e.g., syrinx) or modulate (e.g., beaks) vocalizations 84 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our estimates of phylogenetic inertia provide further evidence that power distribution and spectrotemporal features are minimally constrained in their evolution (i.e., low phylogenetic inertia), suggesting that these features may reflect the plasticity needed to alter song features for inter- and intra-specific competition. Analyses using ppMantel tests showed that body size is correlated with frequency features in our species, a common finding in animals including birds 53 , 84 , 85 . Previous studies suggest that changes in frequency features may be constrained to changes in morphological features associated with body size such as size of the organs that produce (e.g., syrinx) or modulate (e.g., beaks) vocalizations 84 .…”
Section: Discussionsupporting
confidence: 53%
“…Analyses using ppMantel tests showed that body size is correlated with frequency features in our species, a common finding in animals including birds 53 , 84 , 85 . Previous studies suggest that changes in frequency features may be constrained to changes in morphological features associated with body size such as size of the organs that produce (e.g., syrinx) or modulate (e.g., beaks) vocalizations 84 . Relatively small effect sizes for the frequency-to-morphology correlations, however, may suggest that differences in frequency characteristics may be further explained by factors other than the evolutionary changes in body or organ size.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation